The pseudodifferential operator A(x, D). (18th February 2004) - Pathak, R. S.; Pathak, S.
Abstract : The pseudodifferential operator (p.d.o.)A ( x, D ), associated with the Bessel operatord 2 / d x 2 + ( 1 − 4 μ 2 ) / 4 x 2, is defined. Symbol classH ρ, δ m is introduced. It is shown that the p.d.o. associated with a symbol belonging to this class is a continuous linear mapping of the Zemanian spaceH μ into itself. An integral representation of p.d.o. is obtained. Using Hankel convolutionL σ, α p -norm continuity of the p.d.o. is proved.